(untitled) (Journal of Educational Sciences, 2021)
The article examines the role of the quality of spiritual, moral and patriotic education in improving the quality of secondary education, as well as the organization of the educational process in countries with a developed quality of education. The article examines the educational process, the features and its organization in developed countries such as South Korea, Finland, Singapore and Japan. The article reveals the position that the traditions of national education are the basis of the traditions of upbringing in most developed countries. Revealed the similarity of educational systems: the presence of elements of national education and ethnopedagogy; the principles of family education and respect for elders, attention, and care for the younger ones; other principles. The upbringing process is complex, and its results are difficult to evaluate. Family, school, and society make a significant contribution to the upbringing and educational process. If the influence of family, school, and society is inconsistent, we can get negative results and poor quality of education and upbringing. The article presents the results of an experiment in the Turkestan region to improve the quality of spiritual, moral, and patriotic education, the criteria and parameters of the educational dimension used. Key words: secondary education, education, spiritual and moral education, patriotic education, quality of education, experiment.